2D image analysis method for evaluating coarse aggregate characteristic and distribution in concrete. (30th November 2016) - Han, Jianguo; Wang, Kejin; Wang, Xuhao; Monteiro, Paulo J.M.
Highlights: Two-dimensional image analysis method for particle status analysis is developed. Coarse aggregate characteristic and distribution in concrete are analyzed. Information of 2D image analysis and 3D experiment results has good consistency. Image analysis can help to improve concrete quality and optimize mix proportion. Disturbance should be avoid to guarantee coarse aggregate distributing homogeneity. Abstract: Two-dimensional (2D) image analysis method is developed for evaluating coarse aggregate characteristic and distribution in concrete, based on concrete cross-section image. Coarse aggregate characteristic includes particle size, particle grading, particle roundness and particle orientation. Coarse aggregate distribution includes particle distributing homogeneity, particle distance and mortar to coarse aggregate area ratio (MAAR). The 2D image analysis method is performed on one conventional concrete and four self-consolidating concrete. Except exhibiting the ability of the 2D image analysis method, the analysis results also show the consistency of 2D information and 3D information, by comparing particle grading with sieving curve, and MAAR with mortar to coarse aggregate volume ratio (MAVR). Meanwhile, the 2D image analysis method can reveal the influence stochastic error, such as vibration and non-uniform sampling, on the homogeneity of concrete.